Comparative clinical and immunological characteristics of the course of the new coronavirus infection COVID-19 in children of different ages in acute and long-term periods after illness - О. М. Olenkova; О. Р. Kovtun; Ya. B. Beikin; А. S. Sokolova (LLC "Diagnostics and Vaccines", 2023)
The purpose of the study is to establish the clinical and immunological characteristics of COVID-19 in children and to assess the state of the immune system in the long-term period after the infection. Materials and methods. An observational cohort retrospective study was conducted, which included the results of an examination of 87 children with confirmed new coronavirus infection (COVID-19). All patients underwent laboratory examination to assess the state of the immune system at the onset of the disease and 152 ± 11.57 days after the onset of the disease. The control groups consisted of practically healthy children 8-14 (n = 26) and 15-18 years old (n = 33), who had no history of coronavirus infection, which was verified by serological tests. Results. Of the sick people, 72.2% were boys (p < 0.001). The clinical picture of COVID-19 was determined by the presence of intoxication and respiratory syndromes. The main signs were fever, unproductive cough, nasal discharge, pain and/or sore throat. In 35.2% of cases, children had concomitant pathology. At the onset of the disease in patients aged 8-14 years, a decrease in the number of neutrophils (p < 0.001) and their absorption activity (p = 0.01), an increased level of CD3+HLA-DR+ (p < 0.001), and a low level of serum IgM were detected (p < 0.001), were detected the presence of specific IgM to SARS-CoV-2; high content of Circulating immune complexes (p < 0.001). In children aged 15-18 years, an increase in the content of CD3+HLA-DR+ (p < 0.001), TNK-cells (p < 0.05), and a decreased level of total serum IgM and IgG (p < 0.001) were detected. In the long-term period after infection, in patients 8-14 years old, the changes identified at the onset of the disease persist, and there is also a decrease in the number of monocytes (p < 0.05) and an increase in the level of B-lymphocytes (p < 0.05). In the group of 15-18 years old, there was an increase in the bactericidal activity of leukocytes (p = 0.03) and the absorption activity of monocytes (p < 0.01). Conclusion. The disease proceeded mainly in a moderate form. At the initial stage of the new coronavirus infection, there was a deficiency of the humoral component, and in children of early school age, a deficiency of innate immune factors. In the long-term period, deviations in immunogram parameters persist. There is a possibility of the formation of risk groups among children for immune deficiency, which requires additional monitoring and rehabilitation measures.